Characterisation of Pseudomonas chlororaphis subsp. aurantiaca strain Pa40 with the ability to control wheat sharp eyespot disease. (19th September 2013) - Jiao, Z.; Wu, N.; Hale, L.; Wu, W.; Wu, D.; Guo, Y.
Abstract This study details the isolation and characterisation of Pseudomonas chlororaphis subsp. aurantiaca strain Pa40, and is the first to examine P. chlororaphis for use in suppression of wheat sharp eyespot on wheat. Pa40 was isolated during an investigation aimed to identify biocontrol agents for Rhizoctonia cerealis. Over 500 bacterial strains were isolated from the rhizosphere of infected wheat and screened for in vitro antibiosis towards R. cerealis and ability to provide biocontrol in planta. Twenty‐six isolates showed highly antagonistic activity towards R. cerealis, in which Pseudomonas spp. and Bacillus spp. were predominant members of the antagonistic community. Strain Pa40 exhibited clear and consistent suppression of wheat sharp eyespot disease in a greenhouse study and suppression was comparable to that of chemical treatment with validamycin A. Pa40 was identified as P. chlororaphis subsp. aurantiaca by the Biolog identification system combined with 16S rDNA, atpD, carA and recA sequence analysis and biochemical and physiological characteristics. To determine broad‐spectrum applicability and the specific mechanisms involved in Pa40's pathogen suppression this strain was tested for antibiosis towards various phytopathogens and assayed for many biocontrol activities and plant‐beneficial traits. Strain Pa40 inhibited the growth of 10 of 13 phytopathogenic fungal strains and six of eight phytopathogenic bacteria tested. This original work characterises HCN, protease and siderophore production in P. chlororaphis. Each of these characteristics likely contributed to Pa40's biocontrol capabilities as well as stimulation of the hypersensitive response in tobacco and the presence of genes involved in the biosynthesis of phenazine, 2‐hydroxylated phenazine and pyrrolnitrin.